Comparing opportunistic and population-based breast cancer screening programs in China: a systematic review and meta-analysis on 12.98 million women - Mengdan Li; Hongying Wang; Haozhe Piao; Bo Zhu (The Lancet Regional Health. Western Pacific)
Background: In China, the incidence of breast cancer and the disease burden continue to increase. Different screening programs have slightly different implementation plans. This study aims to analyze the screening effects of population and opportunistic breast cancer screening programs in China. Methods: We conducted a systematic review and meta-analysis of studies in multiple literature databases. Studies that were published between January 1, 2010, and June 30, 2023 were retrieved. A random effects model was employed to pool the single group rate, and subgroup analyses were carried out based on screening model, time, process, age, population, and follow-up method. Findings: A total of 47 databases satisfied the inclusion criteria, including 39 for population screening and 8 for opportunistic screening. The cancer detection rate (CDR) in the opportunistic screening group with a sample size of 224,240 was 11.99‰ (95% CI: 5.14‰–21.57‰), and in the population screening group with a sample size of 12,760,718 was 1.32‰ (95% CI: 1.10‰–1.56‰) In subgroup analysis, the CDR of population screening was higher in the urban group (2.28‰, 95% CI: 1.70‰–2.94‰), in the breast ultrasonography (BUS) in parallel with mammography (MAM) group (3.29‰, 95% CI: 2.48‰–4.21‰), and in the second screening follow-up group (2.47‰, 95% CI: 1.64‰–3.47‰), and the proportion of early-stage breast cancer was 85.70% (95% CI: 68.73%–97.29%), 88.18% (95% CI: 84.53%–91.46%), and 90.05% (95% CI: 84.07%–94.95%), respectively. The proportion of early-stage breast cancer in populations screening group was higher than in opportunistic screening group (early-stage 0–I: 49.81%, 95% CI: 44.25%–55.37% VS 35.68%, 95% CI: 25.85%–46.11%; early-stage 0–II: 80.17%, 95% CI: 71.40%–87.83% VS 72.42%, 95% CI: 57.28%–85.57%). Interpretation: There were significant differences in the detection rates of breast cancer and early-stage breast cancer between opportunistic and population screening programs among Chinese women. The results of these population screening studies were influenced by various factors including the screening process, age, population, and follow-up method. Moving forward, China's breast cancer prevention and control efforts should emphasize the advancement of population-based organized screening programs, complemented by opportunistic screening.